Presence of toxic metals in toys for domestic animals: Review - Souza, Nicolli Carriel de; Blaitt, Regina Maria Nascimento Augusto; Grotto, Denise (Pubvet, 2022)
Due to the growing number of dogs and cats in Brazilian households, there was also a growing in industrial/commercial sector focused on these pets. With the resignification of these animals within the families, especially with the "infantilization" process, the industry started to produce clothes, treats, and toys for the owners to buy, reflecting in pets their consumerism and the attribution of affective values. Thus, toys have gained prominence due to their environmental enrichment benefits. However, despite the increase in demand, there is no regulatory legislation for toys designed for pets, setting precedents for contamination that endanger the pets’ health due to unregulated production. It is suggested the presence of toxic metals in unknown concentrations in these objects, because in toys for children there is the presence of these elements in pre-established concentrations aiming at the safety and integrity of the target audience when purchasing these products. The harmful relevance, especially of toxic metals such as lead (Pb), Mercury (Hg), Cadmium (Cd), and Arsenic (As), can induce acute and chronic toxicosis, triggered by the accumulation of these elements in the tissues, damaging the metabolism and normal physiology of the animal. This literature review aims to point out the possible presence of toxic metals in pet toys, as well as to describe laboratory tests to detect these elements.